Ratio Decidendi Terhadap Putusan Pengadilan Negeri Kota Surabaya Nomor 2073/Pid.Sus/2023/Pn.Sby Tentang Pornografi - Afandi, Zainal; Rosando, Abraham Ferry (Media Hukum Indonesia (MHI), 2024)
This research discusses the ratio decidendi in the Surabaya City District Court Decision Number 2073/Pid.Sus/2023/PN.Sby regarding the crime of digital pornography. The ratio decidendi or legal basis used by the judge plays an important role in reaching a fair decision, providing a deterrent effect to the perpetrator, and protecting the victim from the negative impacts of pornography. This research uses normative juridical methods with a case study approach and literature analysis, including Law no. 44 of 2008 concerning Pornography. The research results show that the ratio decidendi used does not only consider punitive aspects but also preventive and educative functions for society. The judge emphasized protecting public morals, protecting victims, as well as providing a strong message regarding the legal consequences of spreading pornographic content. It is hoped that this ratio decidendi can become a legal precedent for similar cases in the future and become the basis for developing more comprehensive regulations in the digital era.